Pengaruh Kesadaran Wajib Pajak, Kualitas PeLayanan Perpajakan Terhadap Penerimaan Pajak Penghasilan Orang Pribadi di KPP Pratama Cibitung - Jarkoni, Jarkoni; Hariansyah, Irene Septy (Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and analyze whether the effect of taxpayer awareness, tax service quality, on individual tax income receipts. Respondents in this study were individual taxpayers at KPP Pratama Cibitung. The number of taxpayers who became the sample of this study were 235 taxpayers at KPP Pratama Cibitung. The sampling method used in this research is random sampling. The data analysis technique used is instrument test (validity test and reliability test), and classical assumption test (normality test, multicollinearity test, and heteroscedasticity test). While the hypothesis test is a partial test (t test), simultaneous test (F test) and the Coefficient of Determination test. The results showed that taxpayer awareness, tax service quality proved to have a significant positive effect on individual income tax receipts simultaneously. Partially, the taxpayer awareness variable has an effect on income tax receipts with a significance of 0.000 for income tax revenues. Meanwhile, the quality of tax services has a significant effect on income tax revenues with a significance value of 0.167 which has the most significant effect. The coefficient of determination is 68.8%.